Population-specific metabolic alterations in professional antigen-presenting cells contribute to sepsis-associated immunosuppression - Schenz, Judith; Uhle, Sandra; Nußhag, Christian; Brenner, Thorsten; Poschet, Gernot; Weigand, Markus A.; Uhle, Florian (Shock, 2020)
Sepsis is a complex host response triggered by an infection, with the patient's immune system between hyper- and hypo-responsiveness being the main reason for the syndromes’ development and propagation. Studies conducted in peripheral blood mononuclear cells uncovered an association between an impaired immunometabolism and the severity and outcome of the disease. With this prospective observational study, we aimed to evaluate the immunometabolic phenotype of monocytes and B cells and its association with the cell function. - Monocytes and B cells were isolated from patients with sepsis (n = 10; onset, days 4 and 8) and healthy volunteers (n = 10) and subsequently analyzed for metabolic changes and human leukocyte antigen-DR (HLA-DR) expression. Contemporaneously, immune checkpoints on monocytes and the ex vivo cytokine responses (interleukins 6 and 8) upon lipopolysaccharide or zymosan stimulation were analyzed. The distribution of B cell subsets was assessed, and plasma levels of immunoglobulins and tricarboxylic acid cycle intermediates were quantified. - Both monocytes and B cells exhibited decreased HLA-DR expression in patients with sepsis. Monocytes displayed a stable upregulated glycolysis while B cells augmented glycolysis and respiration over time. The monocytes’ ability to respond to stimulation was stimuli-dependently reduced but recovered over time. The B cell compartment shifted toward antibody-producing subsets and elevated immunoglobulins within the first days. - Our results provide evidence for the induction of a state of trained immunity in monocytes and an early but transient immunosuppressive phenotype accounting for peripheral sepsis-induced vulnerability to infections. B cells exhibit an unsustainable activation contributing to adaptive immunosuppression.
Gesehen am 01.10.2020